2019
DOI: 10.1002/cam4.1864
|View full text |Cite
|
Sign up to set email alerts
|

Painting a portrait: Analysis of national health survey data for cancer genetic counseling

Abstract: Background Despite a growing body of literature describing the geographic and sociodemographic distribution of cancer genetic testing, work focused on these domains in cancer genetic counseling is limited. Research describing the epidemiology of cancer genetic counseling has mainly focused on isolated populations, a single gender (women) and a single condition (hereditary breast and ovarian cancer). Study findings to date are contradictory, making it unclear what, if any, disparities in receipt of cancer genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…When referred, rates of uptake of genetic counseling in some racial and ethnic minority groups are similar to each other, but in other cases rates of uptake are lower compared with similar groups of White individuals (Forman & Hall, ; Halbert et al, ). In contrast, several studies have demonstrated that Black individuals had a greater likelihood of undergoing genetic counseling when offered (Katz et al, ; Stamp, Gordon, Childers, & Childers, ). While studies have shown varied uptake of referrals to genetic services based on race and ethnicity, the impact of race and ethnicity on the receipt of genetic counseling, and perception of the genetic counseling process and outcome have yet to be systematically examined or comprehensively understood.…”
Section: Introductionmentioning
confidence: 97%
“…When referred, rates of uptake of genetic counseling in some racial and ethnic minority groups are similar to each other, but in other cases rates of uptake are lower compared with similar groups of White individuals (Forman & Hall, ; Halbert et al, ). In contrast, several studies have demonstrated that Black individuals had a greater likelihood of undergoing genetic counseling when offered (Katz et al, ; Stamp, Gordon, Childers, & Childers, ). While studies have shown varied uptake of referrals to genetic services based on race and ethnicity, the impact of race and ethnicity on the receipt of genetic counseling, and perception of the genetic counseling process and outcome have yet to be systematically examined or comprehensively understood.…”
Section: Introductionmentioning
confidence: 97%
“…The knowledge that one or more first‐degree relatives did have cancer is one important factor for the self‐assessment that one could be at risk for getting cancer as well. Indeed, several analyses using data from the large US National Health Interview Survey (NHIS) identified clear gender differences in awareness and use of genetic counseling and testing 11,12 . Male sex was identified as a factor associated with lower awareness regarding cancer genetic testing 11 and another recent analysis of NHIS 2015 data revealed that in the US men had made less use of genetic counseling than women 12 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several analyses using data from the large US National Health Interview Survey (NHIS) identified clear gender differences in awareness and use of genetic counseling and testing. 11,12 Male sex was identified as a factor associated with lower awareness regarding cancer genetic testing 11 and another recent analysis of NHIS 2015 data revealed that in the US men had made less use of genetic counseling than women. 12 Up to now the evidence regarding gender differences in self-reported FHC has not been systematically gathered and analyzed across studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some previously published studies have addressed the association between ethnicity and the probability of receiving genetic counseling and testing [22, 25]. It should be mentioned that while our study relies heavily on the high quality of Swedish health care registries and the possibility to link data from different registries through personal identification numbers, ethnicity is considered sensitive information and could not be extracted on an individual basis for this project.…”
Section: Discussionmentioning
confidence: 99%